From 'Doctor Knows Best' to Dignity: Placing Adults Who Lack Capacity at the Centre of Decisions About Their Medical Treatment. Issue 2 (12th March 2018) - Jackson, Emily
Abstract: In 1989, the House of Lords first derived a 'best interests' test for the medical treatment of adults who lack capacity from the doctrine of necessity and, now codified, the test continues to apply today. The Mental Capacity Act 2005 sets out a non‐exhaustive checklist of relevant considerations, but it gives no particular priority to the patient's wishes. There is also no formal expectation that the patient will participate directly in any court proceedings in which her best interests are to be determined. This article will consider the advantages and disadvantages of providing additional guidance to decision‐makers in order to help them navigate both taking seriously the wishes of people who lack capacity and, at the same time, not abandoning patients who need help and support. More specifically, this article advocates formalising current best practice in the Court of Protection through the introduction of a series of rebuttable presumptions, or starting points.